High pressure-induced mtDNA alterations in retinal ganglion cells and subsequent apoptosis - Sheng-Hai Zhang; Sheng-Hai Zhang; Feng-Juan Gao; Zhong-Mou Sun; Ping Xu; Jun-Yi Chen; Xing-Huai Sun; Xing-Huai Sun; Xing-Huai Sun; Ji-Hong Wu; Ji-Hong Wu; Ji-Hong Wu (Frontiers in Cellular Neuroscience, 2016)
Purpose: Our previous study indicated that mitochondrial DNA (mtDNA) damage and mutations are crucial to the progressive loss of retinal ganglion cells (RGCs) in a glaucomatous rat model. In this study, we examined whether high pressure could directly cause mtDNA alterations and whether the latter could lead to mitochondrial dysfunction and RGC death.Methods: Primary cultured rat RGCs were exposed to 30 mm Hg of hydrostatic pressure (HP) for 12, 24, 48, 72, 96, and 120 hours. mtDNA alterations and mtDNA repair/replication enzymes OGG1, MYH and POLG expressions were also analyzed. The RGCs were then infected with a lentiviral small hairpin RNA (shRNA) expression vector targeting POLG (POLG-shRNA), and mtDNA alterations as well as mitochondrial function, including complex I/III activities and ATP production were subsequently studied at appropriate times. Finally, RGC apoptosis and the mitochondrial-apoptosis pathway-related protein cleaved caspase-3 were detected using a Terminal deoxynucleotidyl transferase dUTP nick end-labeling (TUNEL) assay and western blotting, respectively. Results: mtDNA damage was observed as early as 48 hours after the exposure of RGCs to HP. At 120 h after HP, mtDNA damage and mutations significantly increased, reaching >40% and 4.8±0.3-fold, respectively, compared with the control values. Twelve hours after HP, the expressions of OGG1, MYH and POLG mRNA in the RGCs were obviously increased 5.02±0.6-fold (p<0.01), 4.3±0.2-fold (p<0.05), and 0.8±0.09-fold p<0.05). Western blot analysis showed that the protein levels of the three enzymes decreased at 72 and 120 hours after HP (p<0.05). After interference with POLG-shRNA, the mtDNA damage and mutations were significantly increased (p<0.01), while complex I/III activities gradually decreased (p<0.05). Corresponding decreases in membrane potential and ATP production appeared at 5 and 6 days after POLG-shRNA transfection respectively (p<0.05). Increases in the apoptosis of RGCs and cleaved caspase-3 protein expression were observed after mtDNA damage and mutations.Conclusions: High pressures could directly cause mtDNA alterations, leading to mitochondrial dysfunction and RGC death.